Determinants factors on patients’ satisfaction towards health tourism in Malaysia - Afrina Izzati Mohd Daud; Chua Hui Qi; Fatin Syuhada Shamsul; Muhamad Nurhafiz Norman (2021)
Health is considered one of the most valuable assets to humankind, and this has caused some people to travel in order to improve their health. Tourists has come up that medical tourism is an attractive idea for them to travel around the world border for medical services and becoming a new type of tourism that is popular all around the world. This has increased medical competition industry between countries. Lately, health tourism had become a popular type of tourism in Malaysia. For the sake of having more tourists to visit Malaysia with the purpose of getting medical services, the top priority is to identify the key factors that related to patient satisfaction. This study aims to identify four factors on health tourism that influences on the Malaysian patients’ satisfaction. These factors are medical cost, medical services, health information technology, and destination image. The data is obtained from self-organizing questionnaires to local patients or patients that travel to Malaysia for health purposes tourism. A total number of 200 respondents have involved in this research. The data collected was analyzed using Social Science Statistics Package (SPSS) software and we had used Reliability analysis to test the research model. The research results show that all the factors which are cost, service quality, destination image and health information technology have positive relationship with the patients’ satisfaction and medical services indicates the strongest influence. This study has provided implications for future governments, medical institutions, and researchers to acquire understand the factors that influence patient satisfaction to health tourism in Malaysia